ICD-11 Posttraumatic Stress Disorder and Complex PTSD Among Hospital Medical Workers in China: Impacts of Wenchuan Earthquake Exposure, Workplaces, and Sociodemographic Factors - Li, Sijian; Guo, Chunlan; Chan, Sunshine S. S. (Frontiers in Psychiatry, 2022)
Background: Previous studies have addressed posttraumatic stress disorder (PTSD) following disasters as a public health issue. However, few studies have investigated the long-term effect of disaster exposure on PTSD among hospital medical workers (HMWs). Objectives: This study aimed to study the prevalence of ICD-11 PTSD and complex PTSD (CPTSD) among exposed and non-exposed HMWs 11 years after the Wenchuan earthquake in China, to identify the factors associated with PTSD and CPTSD scores, and to examine the factor structures of PTSD and CPTSD models. Methods: A cross-sectional study was conducted using a self-administered online questionnaire. Two thousand and fifty-nine valid samples were collected from four hospitals in 2019. Descriptive statistical analysis, multivariate regression models, and confirmatory factor analysis (CFA) were performed. Results: The prevalence of PTSD and CPTSD was 0.58% and 0.34%, respectively. The unexposed group reported higher PTSD and CPTSD scores than the exposed group. The type of workplace and marital status were significantly associated with the PTSD and CPTSD scores of HMWs. The CFA results indicated that both the correlated first-order model and the correlated two-layer model were a good fit to explain the structure of PTSD and CPTSD. Conclusion: These findings suggested that few HMWs who were exposed to the Wenchuan earthquake suffered from PTSD or CPTSD 11 years following the disaster. However, psychological support was still necessary for all HMWs, especially for unmarried HMWs who were working in smaller hospitals. Further research is required to analyze mental health status using ICD-11 PTSD and CPTSD, to provide ongoing evidence to help HWMs cope effectively with the challenges of future disasters.